2021
DOI: 10.1111/andr.13116
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the architecture and integrity of frozen‐thawed testicular tissue from (pre)pubertal boys with cancer

Abstract: Background Testicular tissue freezing is proposed for fertility preservation to (pre)pubertal boys with cancer before highly gonadotoxic treatment. Studies accurately comparing human (pre)pubertal testicular tissue quality before freezing and after thawing are exceptional. No study has reported this approach in a systematic manner and routine care. Objectives To assess the impact of a control slow freezing protocol on testicular tissue architecture and integrity of (pre)pubertal boys after thawing. Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…However, slow freezing seems to provide greater protection to testicular tissue than SSV. This is in line with other studies reporting the ability of a slow freezing protocol to maintain tubular architecture and integrity of pre-pubertal human testicular tissue fragments ( 21 , 23 31 ).…”
Section: Cryopreservationsupporting
confidence: 92%
“…However, slow freezing seems to provide greater protection to testicular tissue than SSV. This is in line with other studies reporting the ability of a slow freezing protocol to maintain tubular architecture and integrity of pre-pubertal human testicular tissue fragments ( 21 , 23 31 ).…”
Section: Cryopreservationsupporting
confidence: 92%
“…Keros et al evaluated a protocol for cryopreservation of immature testicular tissue, using sample sizes 1–3 mm × 1–5 mm × 1–7 mm, and demonstrated maintenance of structural integrity and spermatogonia when compared with fresh tissue ( Keros et al , 2007 ). Similarly, a report from eight French CECOS centres comparing pre-pubertal testicular tissue histologically pre- and post-freezing found maintenance of spermatogonial numbers and seminiferous tubule integrity in tissue frozen in 10–15 mg fragments ( Rives-Feraille et al , 2022 ). While these studies did not assess the fertilization capacity of the tissue, the non-human primate tissue fragments used by Fayomi et al (2019) to ultimately yield live offspring fell within the larger size bracket (9–20 mm 3 ); the graft survival and subsequent spermatogenesis suggest that cryoprotectant penetration was adequate in those tissues.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, individual centres have established these analyses also for frozen/thawed testicular tissues, for quality assurance purposes, and have published the results of these assessments ( Keros et al , 2005 , 2007 ; Kvist et al , 2006 ; Gille et al , 2021 ; Kabiri et al , 2022 ; Wang et al , 2022 ). Semi-quantitative analytical techniques have been proposed as a means of standardized quality assessment of freezing techniques and integrity of frozen tissue ( Rives-Feraille et al , 2022 ). However, it should be recognized that the stored material is relatively small and frequent quality assurance during the cryopreservation period will have a significant impact on the amount of material available for future clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is important to highlight that the slow freezing method did not achieve full spermatogenesis and offspring production in human tissue [ 31 ]. Wyns et al discovered that slow freezing can preserve the proliferation capacity of spermatogonial cells even after 6 months of xenografting, which may have beneficial effects on the long-term survival of the tissue.…”
Section: Cryopreservation Strategiesmentioning
confidence: 99%
“…In a study conducted by Rives-Feraille et al in 2021, they cryopreserved and subsequently stored ITT obtained from prepubertal boys with cancer by CSF. Their findings indicated that there was no significant difference in seminiferous tubule integrity between fresh tissue and frozen-thawed tissue [ 31 ].…”
Section: Cryopreservation Strategiesmentioning
confidence: 99%